Literature Review : Strategies for Using Digital Marketing to Improve MSME Performance in Supporting SDGs Programs - Siti Rahayuningsih; Iwan Agus Darmawan; Sri Yuliani Pangesti; Ainun Fuad; Ludi Wishnu Wardana; Bagus Shandy Narmaditya (International Journal of Economics, Management and Accounting, 2024)
The current global phenomenon shows a rapid increase in the adoption of digital technology, which has changed various aspects of life, including the micro, small and medium enterprises (MSMEs) sector. This study aims to examine effective digital marketing strategies to improve MSME performance in supporting the Sustainable Development Goals (SDGs) Program. The novelty of this research lies in a holistic approach that integrates various aspects of digital marketing, in the context of SDGs implementation. The urgency of this research is driven by the urgent need for MSMEs to remain competitive and relevant in the digital era, as well as the crucial role in the national economy and the achievement of SDGs goals. The method used in this study is Systematic Literature Review (SLR) by collecting relevant previous research through publish or perish Then analyze the article and crucify related to keywords. The results show that the use of appropriate digital marketing can help MSMEs contribute more effectively to the achievement of SDGs, especially in terms of poverty alleviation, job creation, and inclusive economic growth. The implications of this research emphasize the importance of policy support and continuous training for MSMEs in utilizing digital technology, as well as collaboration between the public and private sectors to accelerate the digital transformation of MSMEs.